Plumbing engineering design handbook. Volume 3, a plumbing engineer's guide to system design and specifications (American Society of Plumbing Engineers, 2015)
This Handbook is designed to provide accurate and authoritative information for the design and specification of plumbing systems. This book has 11 chapters including such topics as Fire Protection Systems, Plumbing Design for Healthcare Facilities, Treatment of Industrial Waste, Irrigation Systems, Reflecting Pools and Fountains, Public Swimming Pools, Gasoline and Diesel Oil Systems, Steam and Condensate Piping, Compressed Air Systems, Solar Energy, Site Utility Systems, and contains many tables and illustrations. This important reference will benefit engineers, plumbing system designers, architects, plant engineers, inspectors, journeymen, students, contractors, and builders.
Keywords: Plumbing -- Handbooks, manuals, etc.; elektronické knihy; electronic books